2020
DOI: 10.1007/s10854-020-03061-y
|View full text |Cite
|
Sign up to set email alerts
|

Selective laser ablation and patterning on Ag thin films with width and depth control

Abstract: Silver (Ag) films were deposited on glass substrates by radio frequency (RF) magnetron sputtering and then ablated by a 532 nm nanosecond pulsed laser. The effects of laser fluence and defocusing amount on the width and depth of laser-ablated grooves on 100-and 600-nm-thick Ag films were systematically investigated under single-and multi-scan ablation. The results suggested that the Ag films could be successfully removed from the substrate owing to laser-induced thermoelastic force or vaporization. It was conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…P A Danilov et al [68,69] recently measured values between 0.1 and 0.4 J cm −2 on films with a thickness of 50 nm, depending on both temporal duration and dimension of the laser pulse. Considering experiments using ns-laser pulse, L Huang et al [49] observed that a clear ablation pattern could still be formed for a working fluence of 0.1 J cm −2 so that F th is lower this value considering their investigation. Our results are consistent with the literature although none of the cited works refer to a possible thermoelastic effect because the working fluences were too high to observe a pure thermoelastic ablation.…”
Section: Analysis Of Craters Created By Pla On Ag Thin Filmmentioning
confidence: 97%
See 2 more Smart Citations
“…P A Danilov et al [68,69] recently measured values between 0.1 and 0.4 J cm −2 on films with a thickness of 50 nm, depending on both temporal duration and dimension of the laser pulse. Considering experiments using ns-laser pulse, L Huang et al [49] observed that a clear ablation pattern could still be formed for a working fluence of 0.1 J cm −2 so that F th is lower this value considering their investigation. Our results are consistent with the literature although none of the cited works refer to a possible thermoelastic effect because the working fluences were too high to observe a pure thermoelastic ablation.…”
Section: Analysis Of Craters Created By Pla On Ag Thin Filmmentioning
confidence: 97%
“…These images give important information about the origin of the PLA process depending on the working fluence. As explained in [43,49], depending on the working fluence, the increase in temperature at the metal/ substrate interface after absorption of the laser pulse may cause different phenomena. As depicted in figure 4, when the temperature is below the fusion point, a thermoelastic force is induced by PLA, which locally enhances the mechanical stress of the thin film.…”
Section: Analysis Of Craters Created By Pla On Ag Thin Filmmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the research was only performed for simple grooves, and no in-depth study on the processing accuracy and efficiency has been carried out. Jia [6] and Liu [7] adopted a precise removal technology for metal-layer localization based on a numerical control laser to complete the precision processing of typical samples. The three-dimensional metal graphics were precisely joined, with smooth and neat edges.…”
Section: Introductionmentioning
confidence: 99%
“…Transparent conductive oxide (TCO), as a kind of ceramic material, has been widely applied to photoelectric devices such as flat panel displays [1], solar cells [2,3], organic light emitting devices (OLEDs) [4] and photosensors [5], due to its outstanding optical and electrical properties. Indium tin oxide (ITO), which has been most often used in various optoelectronic applications in the past many years, has now been gradually replaced by other TCO materials because of the scarcity and toxicity of the indium element [6,7].…”
Section: Introductionmentioning
confidence: 99%